2019
DOI: 10.1007/s10815-019-01417-w
|View full text |Cite
|
Sign up to set email alerts
|

PEX10, SIRPA-SIRPG, and SOX5 gene polymorphisms are strongly associated with nonobstructive azoospermia susceptibility

Abstract: Purpose Male infertility is a multifactorial syndrome encompassing a wide variety of disorders. A previous Chinese genomewide single-nucleotide polymorphism (SNP) association studies have identified four SNPs (rs12097821 in PRMT6 gene, rs2477686 in PEX10 gene, rs6080550 in SIRPA-SIRPG, and rs10842262 in SOX5 gene) as being significantly associated with risk factors for nonobstructive azoospermia (NOA). However, the results were not fully repeated in later studies, which calls for further investigations. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 23 publications
0
23
0
3
Order By: Relevance
“…PEX10 (Peroxisomal Biogenesis Factor 10) encodes for a protein localized to the peroxisomal membrane and involved in the import of peroxisomal matrix proteins. The gene is highly expressed in testis, and a metaanalysis suggests that PEX10 polymorphisms are associated with male infertility, especially with nonobstructive azoospermia susceptibility [40]. PRR4 gene encodes for Proline-rich protein 4, a poorly characterized protein with very low expression in most human tissues, except for tear fluid [41].…”
Section: Agingmentioning
confidence: 99%
“…PEX10 (Peroxisomal Biogenesis Factor 10) encodes for a protein localized to the peroxisomal membrane and involved in the import of peroxisomal matrix proteins. The gene is highly expressed in testis, and a metaanalysis suggests that PEX10 polymorphisms are associated with male infertility, especially with nonobstructive azoospermia susceptibility [40]. PRR4 gene encodes for Proline-rich protein 4, a poorly characterized protein with very low expression in most human tissues, except for tear fluid [41].…”
Section: Agingmentioning
confidence: 99%
“…The etiology of NOA includes genetic abnormalities, and infectious and environmental causes 2 – 4 . A few studies have reported that genetic factors are involved in the development of NOA, including Y-chromosome microdeletions and rare mutations, based on familiar case reports and mouse model analysis 5 9 . However, the molecular basis of NOA is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The world Health Organization estimate that 10–15% of couples struggle with infertility issues and male factors account for about half of all infertility cases [2, 3] Unfortunately, nearly 60–75% of male infertility is unexplained or idiopathic, since the molecular mechanisms underlying the defects remain unknown [4, 5]. Non-obstructive azoospermia (NOA) is the most severe manifestation of male infertility which spermatogenesis process is disrupted [6, 7], it affects 1% of males and 10% of those who seek fertility assistance [8]. It also demonstrated that NOA accounts for approximately 60% azoospermia in which spermatogenesis process is inactive and thus sperm cells are not generated [9].…”
Section: Introductionmentioning
confidence: 99%